THE INTEGRATION OF PROBLEM-SOLVING SKILLS IN ENGLISH IN ACADEMIC DISCOURSE SYLLABUS AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Kamavia Prasia Aspastur; Siti Drivoka Sulistyaningrum (LET: Linguistics, Literature and English Teaching Journal, 2021)
Problem-solving skills have become the essential skill needed in the recent years. However, less attention has been paid to the integration of problem-solving skills in the course syllabus. Hence, this study aims to discover the extent to which problem-solving skills are integrated in the syllabus of “English in Academic Discourse” course and which components of the syllabus integrate problem-solving skills. The 21 words/phrases/sentences that indicate problem-solving skills in the syllabus components of English in Academic Discourse course in English Language Education Study Program were analyzed using problem-solving skills frameworks and indicators obtained from PISA (OECD, 2013), Trilling & Fadel (2009), and Partnership for 21st Century Learning Framework (P21, 2019). Qualitative content analysis is used as the methodology of this study and deductive content analysis by Mayring (2014) is used as the data analysis procedure of this study. The findings of this study show that all of the problem-solving skills indicators–exploration, understanding, representation, solution identification, planning, plan’s execution, monitoring and reflection–are integrated explicitly and implicitly in the course syllabus components. However, only five out of eleven syllabus components–basic information of the course, learning outcomes, course objectives, learning method, and course activities–integrate it.